Impact of the HRM content (i.e. practices) and process (i.e. strength) on individual and organizational outcomes, in the hotel industry - Madeira, Sara de Oliveira Barradas Filipe (2014)
A Work Project, presented as part of the requirements for the Award of a Masters Degree in Management from the NOVA – School of Business and Economics